A formação em serviço social: superação ou reprodução do conservadorismo? - Querino, Anmaina Andriola (2014)
Training in Social Work today has faced a number of difficulties inherent in the overgrowth of courses across the country, which are part of the commercialization strategies of education by the business receiving the consent of the State for the conduct of Education Policy in contemporary, reaching all levels, especially higher education. Featuring the neoliberal scenario, these practices, and cause the uncontrolled growth of higher education institutions, spreading an ideology that seeks only the interests of capital. In this sense, the proliferation of traditional conservative thought is reinforced which so influenced the profession since its appearance confronting the critical dialectical thinking adopted by the professional category from your breach of movement. It was in order to address this problem that is born our subject: formation in Social Work: overcoming or reproduction of conservatism? Therefore, delimited as research space, private schools of social work, classroom and distance, located in the hinterland of Paraiba. In this perspective, the study was developed in two methodological steps: literature review based on diverse texts relevant to the proposed theme and field research through interviews with the subjects participants of this process of training in Social Work: teachers, students and course coordinators -face private institutions and the market town of Cajazeiras / PB. The main results identified a fragmentation in the training of social workers resulting from various repercussions and strategies used by the capitalist dynamics in conducting this process in the two types of education: classroom and distance. However, in the first, proved to be an intense effort on the part of teachers, inserted in local research, disseminate more knowledge based on global reality, allowing the seizure of critical dialectical thought, in a demonstration of concern and commitment that category teaching to the defense of his Political Ethics Project and a more qualified training, however, it is concluded that this effort has been challenged by the printed conservative functional logic the private character of educational institutions.